Deformation behavior relationship between tensile and nanoindentation tests of SAC305 lead-free solder wire. Issue 3 (21st December 2017) - Abdullah, Izhan; Zulkifli, Muhammad Nubli; Jalar, Azman; Ismail, R.
Abstract : Purpose: The relationship between the bulk and localized mechanical properties is critically needed, especially to understand the mechanical performance of solder alloy because of smaller sizing trend of solder joint. The purpose of this paper is to investigate the relationship between tensile and nanoindentation tests toward the mechanical properties and deformation behavior of Sn-3.0Ag-0.5Cu (SAC305) lead-free solder wire at room temperature. Design/methodology/approach: Tensile test with different strain rates of 1.5 × 10-4 s-1, 1.5 × 10-3 s-1, 1.5 × 10-2 s-1 and 1.5 × 10-1 s-1 at room temperature of 25°C were carried out on lead-free Sn-3.0Ag-0.5Cu (SAC305) solder wire. Stress–strain curves and mechanical properties such as yield strength (YS), ultimate tensile strength (UTS) and elongation were determined from the tensile test. Load-depth (P-h) profiles and micromechanical properties, namely, hardness and reduced modulus, were obtained from nanoindentation test. In addition, the deformation mechanisms of SAC305 lead-free solder wire were obtained by measuring the range of creep parameters, namely, stress exponent and strain rate sensitivity, using both of tensile and nanoindentation data. Findings: It was observed that qualitative results obtained from tensile and nanoindentation tests can be used to identify the changes of the microstructure. The occurrence of dynamic recrystallization and the increase of ductility obtained from tensile test can be used to indicate the increment of grain refinement or dislocation density. Similarly, the occurrence of earliest pop-in event and the highest occurrence of pop-in event observed from nanoindentation also can be used to identify the increase of grain refinement and dislocation density. An increment of strain rates increases the YS and ultimate UTS of SAC305 solder wire. Similarly, the variation of hardness of SAC305 solder wire has the similar trend or linear relationship with the variation of YS and UTS, following the Tabor relation. In contrast, the variation of reduced modulus has a different trend compared to that of hardness. The deformation behavior analysis based on the Holomon's relation for tensile test and constant load method for nanoindentation test showed the same trend but with different deformation mechanisms. The transition of responsible deformation mechanism was obtained from both tensile and nanoindentation tests which from grain boundary sliding (GBS) to grain boundary diffusion and dislocation climb to grain boundary slide, respectively. Originality/value: For the current analysis, the relationship between tensile and nanoindentation test was analyzed specifically for the SAC305 lead-free solder wire, which is still lacking. The findings provide a valuable data, especially when comparing the trend and mechanism involved in bulk (tensile) and localized (nanoindentation) methods of testing.